Single-Center Experience With Epigenetic Treatment for Juvenile Myelomonocytic Leukemia - Marcu, Andra; Colita, Andrei; Radu, Letitia Elena; Jercan, Cristina Georgiana; Bica, Ana Maria; Asan, Minodora; Coriu, Daniel; Tanase, Alina Daniela; Diaconu, Carmen C.; Mambet, Cristina; Botezatu, Anca; Pasca, Sergiu; et al. (Frontiers in Oncology, 2020)
Background: Juvenile myelomonocytic leukemia (JMML) is a rare myelodysplastic/myeloproliferative neoplasm diagnosed in young children, characterized by somatic or germline mutations in the RAS pathway with subsequent hyperactivation of this pathway. Available data has shown that aberrant DNA methylation plays a significant role in JMML pathogenesis, suggesting a potential benefit of hypomethylating agents (HMA) in JMML treatment. Nonetheless, hematopoietic stem cell transplantation (HSCT) still represents the only curative option for JMML, thus HMA being of potential use to bridge to transplant. Aim. The aim of the current study was to report the results of HMA-based therapy with 5-azacytidine (AZA) in 3 JMML patients treated in a single center that did not participate in EWOG-MDS study. Methods: The diagnosis and treatment response were evaluated according to international consensus criteria. AZA 75 mg/m2 intravenous (i.v.) was administered once daily on days 1-7 of each 28-day cycle. All patients were monitored for hematologic response, spleen size and evolution of extramedullary disease. Quantitative PCR at diagnosis and qualitative PCR were performed after the 3rd AZA cycle and before SCT to evaluate the molecular alterations and genetic response. Results: Three patients diagnosed with JMML were treated with AZA (off-label indication) in Pediatric Department of Fundeni Clinical Institute, Bucharest, Romania between 2017-2019. There were 2 females and 1 male with of 2, 11 and 16 months of age. The cytogenetic analysis showed normal karyotype in all patients. Molecular analysis confirmed KRAS G13D mutation in 2 patients and NRAS G12D mutation in one patient. The clinical evaluation showed important splenomegaly and hepatomegaly in all 3 patients. One patient received AZA for early relapse after haploidentical HSCT and the other 2 patients received upfront AZA, as bridging therapy before HSCT. After HMA therapy, 2/3 patients achieved clinical partial response (cPR), 1/3 had clinical stable disease (cSD) and all had genetic stable disease (gSD) after 3 cycles and were able to receive the planned HSTC. One patient achieved clinical and genetic complete response before HSCT. During 22 cycles of AZA there were only 4 adverse events, but only one determined dose reduction and treatment delay.